Exploring Bangladeshi university students’ willingness to communicate (WTC) in English classes through a qualitative study - Alam, Md Rabiul; Ansarey, Diana; Abdul Halim, Huzaina; Rana, Md Masud; Milon, Md Rashed Khan; Mitu, Rabeya Khatun (Asian-Pacific journal of second and foreign language education, 2022)
English is regarded as a compulsory subject in Bangladesh, which learning starts at the very early stage of a learner. However, after spending almost 12 years in learning English, learners’ oral skill is not seen up to the mark when they enter the university for tertiary education. Sometimes, they are noticed to have their unwillingness to communicate with others. Hence, the current study aims to explore the experiences of Bangladeshi university students’ willingness to communicate (WTC) by employing a multiple case study method. 10 undergraduate students from a private university were interviewed. Apart from semi-structured interview, classroom observations were also carried out for data collection. The obtained data were analysed through the content analysis process. The findings show that students’ earlier experiences of learning English have been positive; however, they think grammar-based English learning is an obstacle in the development of their oral communication. The study also reveals that learners’ WTC is greatly influenced by classroom environment that enhances or declines their interest to communicate with others. Based on the findings, the study suggests that incorporating more drills in English classes by engaging learners with real-life based conversations, dialogues and so forth can enhance learners’ WTC. Hence, learners’ real voice would help the policymakers and language instructors to take the issue into consideration and way-out timely measures.